2016
DOI: 10.1161/hypertensionaha.115.06881
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2–Receptor Agonist C21 Reduces Proteinuria and Oxidative Stress in Kidney of High-Salt–Fed Obese Zucker Rats

Abstract: Oxidative and nitrosative stress have been implicated in high sodium diet (HSD)-related hypertensive renal injury. In the present study we investigated AT2R-mediated renoprotection in obese Zucker rats fed HSD. Obese Zucker rats were fed normal sodium-diet (NSD) or HSD 4%, for 14 days, with/without AT2R agonist C21, delivered subcutaneously via osmotic pump, 1 mg/kg/day. Compared to NSD controls, HSD rats exhibited increase in cortical NADPH oxidase activity, urinary H2O2 and 8-isoprostanes, which were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 70 publications
(76 reference statements)
2
41
0
1
Order By: Relevance
“…Compound 21 dose-dependently inhibits tumor necrosis factor-alpha (TNFα)-induced interleukin 6 production and nuclear factor κB in primary human and murine dermal fibroblasts [130], decreases early renal inflammatory responses in renovascular hypertension via production of NO and cGMP [131,132], inhibits endothelial inflammation and leukocyte adhesion in human umbilical vein endothelial cells (HUVECs) and in ApoE −/− mice [133], and prevents vascular dementia induced by bilateral common carotid artery stenosis in mice [134]. Additionally, Compound 21 is protective against high salt diet-induced kidney injury in obesity Zucker rats [135]. Whether Compound 21 is antihypertensive in animal models and humans in vivo remains uncertain despite the well-recognized vasodepressor and natriuretic effects of AT 2 receptor activation [94,136].…”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 21 dose-dependently inhibits tumor necrosis factor-alpha (TNFα)-induced interleukin 6 production and nuclear factor κB in primary human and murine dermal fibroblasts [130], decreases early renal inflammatory responses in renovascular hypertension via production of NO and cGMP [131,132], inhibits endothelial inflammation and leukocyte adhesion in human umbilical vein endothelial cells (HUVECs) and in ApoE −/− mice [133], and prevents vascular dementia induced by bilateral common carotid artery stenosis in mice [134]. Additionally, Compound 21 is protective against high salt diet-induced kidney injury in obesity Zucker rats [135]. Whether Compound 21 is antihypertensive in animal models and humans in vivo remains uncertain despite the well-recognized vasodepressor and natriuretic effects of AT 2 receptor activation [94,136].…”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%
“…By contrast, Kemp et al demonstrated that C21 lowered blood pressure in ANG II-dependent hypertensive rats and mice through AT 2 receptor-mediated natriuresis [24,94]. Taken together, the available evidence suggests that it is unlikely that Compound 21 may be useful as an antihypertensive agent, but it may be used as a potentially therapeutic agent to help prevent and treat hypertension-induced cardiovascular and kidney organ damages through its anti-fibrotic and anti-inflammatory actions [131,133,135,136], or to counteract AT 1 receptor-mediated ANG II-dependent hypertension [24,94]. …”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%
“…AT 2 Rs have anti-inflammatory, anti-proliferative and anti-fibrotic effects and may protect against oxidative stress (4850). A recent report sheds light on the pathophysiology of the renal dysfunction in obese Zucker rats fed HSD and demonstrates the attenuation of the renal target organ damage with AT 2 R activation via C-21 (**51). HSD rats exhibited an increase in cortical nicotinamide adenine dinucleotide phosphate osidase activity, urinary hydrogen peroxide, and 8-isoprostanes and severe glomerulosclerosis, interstitial fibrosis reduction in glomerular filtration rate, urinary protein leak, and activity of N-acetyl-β-D-glucosaminidase, a lysosomal marker of tubular damage (**51).…”
Section: Beneficial Effects Of At2r Activation In Obesity/metabolic Smentioning
confidence: 99%
“…It is noteworthy that AT2R are upregulated during certain pathological conditions, such as myocardial infarction, vascular injury, brain ischemia, and renal failureThese findings made the AT2R an even more attractive target for drug therapy. The potent AT2R agonist C21 ( 8 ) has been studied in a large number of models and has contributed considerably to the present view on the AT2R as a drug target . Recently an impressive number of articles were disclosed on the biological effects exerted by 8 which reflect the current interest in selective AT2R agonists .…”
Section: Introductionmentioning
confidence: 99%
“…Compound 8 can prevent renal inflammation in the 2‐kidney, 1‐clip hypertension rat model and exerts protective actions in experimental diabetic nephropathy models in rats and mice by inhibiting renal fibrosis, oxidative stress, and inflammation . In this context, there is an evidence suggesting that the AT1R antagonist / AT2R agonist combination might be even more effective in delaying the frequently observed progression of nephropathy associated with diabetes type II than one drug alone . It has also been proposed that a combination of an AT1R antagonist and an AT2R agonist, like 8 could reduce the potential risk of the metabolic complications associated with obesity .…”
Section: Introductionmentioning
confidence: 99%